Optimal analysis for facility configuration and energy management on electric light commercial vehicle charging. (1st May 2022) - Tang, Yanyan; Zhang, Qi; Wen, Zongguo; Bunn, Derek; Martin, Jesus Nieto
Abstract: Whilst the widespread adoption of electric vans is necessary to improve urban air quality and reduce carbon emissions, it is also self-evident that adequate charging stations are a precondition. However, the investment case for basic charging stations without public subsidies is challenging. In the context of a London case study, four business models are compared, which integrate solar power generation and new/second-life battery storage system with the basic charging facilities. Considering the uncertainties of electricity tariff and solar generation, the optimal infrastructure investment and operational planning has been formulated as a two-stage stochastic optimization model. The results show that: (i) in the integrated business models, the return on investment and charger installations could be increased by up to 5.39% and 17.06% respectively, and the carbon intensity could be reduced by up to 8.13%; (ii) the nondiscriminatory grant annualized as 50 £ is not sufficient, and a differentiated government subsidy policy may be more conducive to achieving a positive return on investment, such as 50 £ for fast chargers and 100 £ for rapid chargers; (iii) in the integrated business models, fast chargers undertake more vehicle-to-grid electricity exchange with the pattern adoption rate increased by up to 52.38%, while rapid chargers mainly ensure the timely charging completion with the usage frequency increased by up to 2.82%. Highlights: The enhanced benefits of public charging stations in four business models are compared. A two-stage model regarding the infrastructure investment and operational planning is formulated. The uncertainties of electricity tariff and solar generation are considered for more realistic simulations. The integrated business models are conducive to increasing the investment viability and reducing the carbon intensity.